Effects of prolonged sedimentation from permafrost degradation on macroinvertebrate drift in Arctic streams. Issue Volume 66:Issue S1(2021) Supplement (3rd December 2020) - Levenstein, Brianna; Lento, Jennifer; Culp, Joseph
Abstract: Retrogressive thaw slumps are areas of unstable degraded permafrost that often drain into nearby watersheds, leading to increased sediment loads and changes in water quality. Thaw slumps are prevalent across the Arctic, including western Canada, Alaska, and Russia, and high‐altitude areas of western China. Over the past several decades, increased temperatures and precipitation in the Arctic have led to increases in the size and frequency of thaw slumps. Our study explored the effects of prolonged sedimentation from thaw slumps in the Peel Plateau, NWT, Canada on benthic macroinvertebrate drift, an important biological function of stream ecosystems. Though sedimentation is known to initiate a catastrophic drift response, studies have generally not considered the drift response to ongoing, long‐term perturbation. Drift densities and sediment loads were measured using drift nets and sediment traps at paired sites upstream and downstream of thaw slumps. We compared drift densities and sediment loads between sites and examined how drift differed over a fine‐sediment gradient. The amount of suspended and settling fine sediments increased significantly at downstream sites. Drift densities decreased at downstream sites; however, when drift was corrected for benthic abundance at each site, there was an increase in proportional drift density associated with increased fine sediments. These results indicate that prolonged impacts from thaw slumps result in lower macroinvertebrate abundance and higher proportional drift relative to undisturbed sites. Ultimately, increased sediment loads from thaw slumps represent a chronic stressor that will continue to prevent recovery of macroinvertebrate communities at impacted sites until these features stabilize.